Effects of pomegranate seed oil on metabolic state of patients with Type 2 diabetes mellitus - Zahra Faghihimani; Parvin Mirmiran; Golbon Sohrab; Bijan Iraj; Elham Faghihimani (International Journal of Preventive Medicine, 2016)
Background: Rapid increasing prevalence of diabetes mellitus is a serious health concern in the world. New data determined that the pathogenesis of diabetes mellitus is chronic low-grade inflammation, resulting insulin resistance. Pomegranate seed oil (PSO) has anti-inflammatory effects; though it may reduce insulin resistance and improve glycemia in diabetes mellitus. The present study has been designed to investigate the effects of PSO as a natural dietary component on metabolic state of patients with Type 2 diabetes mellitus. Methods: In a randomized double-blind clinical trial study, 80 patients (28 men) with Type 2 diabetes were randomly allocated to the intervention and control groups. The intervention group consumed PSO capsules, containing 1000 mg PSO twice daily (2000 mg PSO), whereas controls take placebo for 8 weeks. The participants followed their previous dietary patterns and medication use. Dietary factors and metabolic factors including lipid profile, fasting plasma sugar, and insulin and were assayed at the baseline and after 8 weeks. Results: Participants in two intervention and control group were similar regarding anthropometric and the dietary factors at baseline and after trial (P > 0.05). Mean level of total cholesterol, triglyceride, low-density lipoprotein-cholesterol, and high-density lipoprotein was not different significantly between groups after trial (P > 0.05). Consumption of PSO did not significantly affect the levels of parameters such as fasting blood sugar (FBS), insulin, HbA1c, alanine transferase, and homeostasis model assessment-insulin resistance. Conclusions: Consumption of 2000mg PSO per day for 8 weeks had no effect on FBS, insulin resistance and lipid profile in diabetic patients.